x(x-6)(x-2)-72=0

Simple and best practice solution for x(x-6)(x-2)-72=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x-6)(x-2)-72=0 equation:


Simplifying
x(x + -6)(x + -2) + -72 = 0

Reorder the terms:
x(-6 + x)(x + -2) + -72 = 0

Reorder the terms:
x(-6 + x)(-2 + x) + -72 = 0

Multiply (-6 + x) * (-2 + x)
x(-6(-2 + x) + x(-2 + x)) + -72 = 0
x((-2 * -6 + x * -6) + x(-2 + x)) + -72 = 0
x((12 + -6x) + x(-2 + x)) + -72 = 0
x(12 + -6x + (-2 * x + x * x)) + -72 = 0
x(12 + -6x + (-2x + x2)) + -72 = 0

Combine like terms: -6x + -2x = -8x
x(12 + -8x + x2) + -72 = 0
(12 * x + -8x * x + x2 * x) + -72 = 0
(12x + -8x2 + x3) + -72 = 0

Reorder the terms:
-72 + 12x + -8x2 + x3 = 0

Solving
-72 + 12x + -8x2 + x3 = 0

Solving for variable 'x'.

The solution to this equation could not be determined.

See similar equations:

| 10x+3y-50=0 | | x^3-12x^2+38x-14=0 | | X+3=8-2xk | | 3+15a+18b= | | X+3=8-2x | | x-36=x^2-11x | | x-36=x^2-11 | | -4a+4+5a=6-27 | | 5(2x+3)-8x=7 | | 15r^2+10rs+6rs+4s^2= | | 3.5=3(4+.5) | | 14.1-7.1(x+0.9)=12-5(x+3) | | x^2-x-4=20 | | k^2-6k-143=0 | | X^2-(x-2)(x-2)=20 | | 69=x+(y-7) | | -4(x+2)=3y | | x=(y-7) | | x(x+3)=2(x+3)(x-1)+126 | | 5r+10=60 | | 12=2x+y | | D=-4x^2+9x-4-x^2+4x+4 | | (3x+7)(4x+2)= | | 5x(x+2)=175 | | x+(y-7)=69 | | 4x(1-x)=0.88 | | (9x+3)(x+9)= | | 11x-4x=6 | | 4x-4x^2=0.88 | | 12a^2-18a/2a-3 | | (4/7)x=400 | | 1/4=3/5x-5 |

Equations solver categories